The Influence of Career Development, Work Motivation, Work Flexibility on Employee Performance and Satisfaction as Mediation: (Case Study at the Labuan Bajo Tourism Office) - Ogi, Igenasius; Komalasari, Yeyen; Budi Santoso, R Tri Priyono; Joko Adinegara, Gusti Ngurah (Eastasouth Institute, 2024)
The purpose of this study was to examine the effect career development, work motivation, and work flexibility on employee performance with job satisfaction as an intermediary variable at the Labuan Bajo Tourism Office, West Manggarai. This quantitative study, using a questionnaire from 31 ASN employees and analyzed with SEM-PLS, found that career development, work motivation, and work flexibility all positively and significantly affect employee performance and job satisfaction at the Labuan Bajo Tourism Office, West Manggarai. Additionally, job satisfaction mediates the effects of these factors on employee performance.